2022
DOI: 10.3389/fpubh.2022.1055712
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood social capital and self-rated mental health: Disparities between migrants and native residents in Beijing

Abstract: IntroductionAlthough the impact of neighborhood social capital on mental health has long been recognized, the extent to which the impact differs between immigrants and local residents remains a puzzle. This study aims to bridge the gap by comparing internal migrants who are restricted by their household registration (hukou) status, and urban natives in China.MethodsUsing self-rated mental health and social capital survey data collected in 26 neighborhoods in Beijing, this study examines the mental health outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
3
1
Order By: Relevance
“…The difference in social capital was positively associated with both the inequality in anxiety and loneliness between temporary migrants and non-migrants. Contrary to previous studies [ 5 , 40 ], better social capital was observed in permanent migrants compared to non-migrants. Generally, migrants with higher social capital were more likely to have local hukou and be permanent migrants [ 9 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The difference in social capital was positively associated with both the inequality in anxiety and loneliness between temporary migrants and non-migrants. Contrary to previous studies [ 5 , 40 ], better social capital was observed in permanent migrants compared to non-migrants. Generally, migrants with higher social capital were more likely to have local hukou and be permanent migrants [ 9 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Social capital is an important determinant of inequalities in mental health [ 5 , 38 40 ]. Consistent with previous studies on Chinese internal migrants [ 38 ], temporary migrants reported poorer social capital than non-migrants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations